A fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger and a preparation method thereof
By combining modified silicone resin and modified silica, combined with "N-element"-containing silane coupling agent and phenyl silane coupling agent, the existing superhydrophobic coating has been solved, and the problems of poor adhesion, poor wear resistance and fluorine element are achieved, and a fluorine-free superhydrophobic coating with high adhesion, weather resistance and wear resistance are achieved. It is suitable for frost suppression and defrost applications of heat exchangers.
Patent Information
- Application Number
- CN202411669387.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-04
AI Technical Summary
The existing superhydrophobic coatings have poor adhesion, poor wear resistance and harmful fluorine in applications, resulting in environmental protection and performance problems.
Modified silicone resin and modified silica are used as main components, and the adhesion and wear resistance of the coating are enhanced by the introduction of "N-element"-containing silane coupling agent and phenyl silane coupling agent, and the mechanical strength of the coating is improved by micron-scale zirconium oxide particles.
The high adhesion, weather resistance and wear resistance of the fluorine-free wear-resistant superhydrophobic coating is achieved, which extends the heat exchanger surface to delay the growth of the frost layer, improves the defrost efficiency, and reduces the frost accumulation rate.
Smart Images

Figure CN119752268A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new materials, and in particular to a fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger and a preparation method thereof. Background Art
[0002] Superhydrophobic coatings have attracted much attention due to their potential applications in solar power generation equipment, metal corrosion protection, communication equipment and new energy. At present, the field believes that the combination of surface micro-nanostructures and low surface energy substances can obtain superhydrophobic properties. There are many ways to achieve micro-nanostructures, such as template method, photolithography, plasma etching technology, etc. Superhydrophobic surfaces can be achieved by introducing low surface energy substances (such as long-chain fatty acids, polysiloxanes and fluorinated compounds) to modify the rough surface. Among them, fluorinated compounds have attracted widespread attention in the field of superhydrophobicity due to their mechanical strength and excellent low surface energy. Because they have a low-polarity "fluorine protective layer" to protect the carbon chain from mechanical and chemical changes, thus forming a hydrophobic substance with extremely low surface energy. The stable fluorinated groups in fluorinated silanes reduce the van der Waals potential, and the resulting electrostatic interaction limits the contact between the solid phase and the liquid phase, and also limits the interaction between fluorinated silanes and other material groups, which seriously limits functional applications. Fluorine-containing resin is a polymer material with special properties and high value. However, due to the strong electronegativity and small atomic radius of fluorine atoms, fluorine-containing resin has low viscosity and low friction, and poor adhesion to the substrate. In recent years, many studies have been conducted on the environmental and health effects of fluorine-containing compounds. Fluorine-containing compounds are not only expensive, but also have adverse effects on the environment. Therefore, there is an urgent need to develop a super-hydrophobic coating that does not contain fluorine elements and has excellent anti-corrosion properties.
[0003] Silicone resin can achieve excellent properties such as corrosion resistance, flame retardancy, and hydrophobicity. However, in practical applications, most of them lack mechanical durability, especially the disadvantage of poor adhesion on the substrate. Moreover, super-hydrophobic coatings based on silicone resins are often not wear-resistant, and the contact angle decreases sharply with the increase in wear. Therefore, different functionalized functional groups are introduced into silicone resins to enhance adhesion to different substrates and enhance the interaction between different components of the coating, so that the weather resistance and wear resistance of the surface of the super-hydrophobic coating can be achieved.
[0004] The application of electric vehicles is one of the ways to achieve green and sustainable development. One of the key challenges of electric vehicles is the heating / cooling inside the car, and traditional methods consume a lot of electricity. If frost appears on the evaporator, it will cause the heating capacity to drop by 30-57%. In addition, the energy consumed by the defrost cycle accounts for more than 12.9% of the total heat, resulting in a serious reduction in the driving range of electric vehicles. Frosting blocks air circulation and reduces the efficiency of heat exchange. As the frost layer accumulates in the heat exchanger, the air side pressure drop increases with the thickness of the frost layer, and this accumulation may cause complete system failure. Many scholars have proposed methods to delay the growth of frost layers, such as using micromachining, dehumidifiers, heaters, or electric fields. These active methods can effectively prevent or delay frost formation, but they are costly due to the need for high-quality electricity to work. Therefore, the passive method of coating the heat exchanger with hydrophobic materials is more attractive than the above methods because it does not require additional energy consumption. Superhydrophobic surfaces can promote the jumping of condensation droplets, thereby delaying the growth of frost layers. Properly designed superhydrophobic surfaces can not only improve the condensation heat transfer efficiency, but also delay the heterogeneous nucleation of ice, reduce the density of frost layers, and significantly reduce the frost accumulation rate. The superhydrophobic surface can also improve the defrosting efficiency by reducing the adhesion between the frost layer and the substrate surface, thereby more effectively removing condensed water and defrosting residual water.
[0005] The market needs a super-hydrophobic coating that does not contain fluorine elements and has excellent anti-corrosion properties, can improve weather resistance and wear resistance, and can improve defrosting efficiency. The present invention solves such problems. Summary of the invention
[0006] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide a fluorine-free, wear-resistant, super-hydrophobic coating that can be applied to a heat exchanger and a preparation method thereof. The coating of the present invention improves adhesion and mechanical strength; does not contain fluorine elements, solving the problem that the raw materials of market products are not environmentally friendly; has excellent corrosion resistance, weather resistance, and wear resistance; prolongs the delay of frost layer growth on the surface of the heat exchanger, solves the problem of reduced heat exchange efficiency, and can be used to remove condensed water and defrosting residual water.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A fluorine-free wear-resistant super-hydrophobic coating that can be applied to a heat exchanger, the formula of which includes: modified PASR, modified silicon dioxide, and micron-sized zirconium oxide particles in a mass ratio of 20-30:8-15:0.56-1.05; the formula of the modified PASR includes: phenyl vinyl silicone resin PASR, acrylic acid, acrylamide, vinyl epoxy compound, and vinyl-terminated polydimethylsiloxane in a mass ratio of 1.15-2:0.05-0.16:0.12-0.28:0.9-2.3:2.34-4.
[0009] The aforementioned fluorine-free wear-resistant super hydrophobic coating that can be applied to a heat exchanger, the modified PASR formula also includes: a catalyst; the catalyst is azobisisobutyl cyanide with a mass fraction of 0.04-0.2wt%.
[0010] The aforementioned fluorine-free wear-resistant super hydrophobic coating can be applied to a heat exchanger, wherein the phenyl vinyl silicone resin PASR is prepared from a vinyl silane coupling agent and a phenyl-containing silane coupling agent in a molar ratio of 2.5:1-4.5:1.
[0011] The aforementioned fluorine-free wear-resistant super hydrophobic coating can be applied to heat exchangers. The modified silica is prepared by dispersing 7-15 parts of hydrophilic silica nanoparticles in 35-55 parts of toluene and stirring, and then adding 9.115-31.9025 parts of a silane coupling agent containing "N element", and then heating, stirring, centrifuging, washing, and drying.
[0012] The aforementioned fluorine-free wear-resistant super hydrophobic coating that can be applied to a heat exchanger, the silane coupling agent containing "N element" is 3-aminopropyl triethoxysilane, diethylenetriamine propyl trimethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl methyl diethoxysilane, N-(2-aminoethyl-3-aminopropyl) methyl dimethoxysilane, N-(2-aminoethyl-3-aminopropyl) trimethoxysilane, amino-terminated polydimethylsiloxane, 3-(methacryloyl chloride) propyl trimethoxysilane, or 3-
[0013] (Methacryloyl chloride)propylmethyldimethoxysilane or a combination of several thereof.
[0014] The aforementioned fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger further comprises: 0.02-0.07 wt % of an auxiliary agent, wherein the auxiliary agent comprises: a dispersant, a defoaming agent, and a silicone lubricant.
[0015] The aforementioned fluorine-free wear-resistant super hydrophobic coating that can be applied to a heat exchanger also includes: a solvent mixture for diluting the modified PASR, wherein the solvent mixture is 99.5wt% ester solvent and 99.0wt% aromatic hydrocarbon solvent in a mass ratio of 1:1; the ester solvent includes: one or a combination of ethyl acetate, n-propyl acetate, butyl acetate or isobutyl acetate; the aromatic hydrocarbon solvent is one or a combination of toluene or xylene.
[0016] A method for preparing a fluorine-free wear-resistant super-hydrophobic coating that can be applied to a heat exchanger, the preparation process comprising the following steps:
[0017] Step 1, preparation of modified silica:
[0018] Dispersing 4-11 parts of hydrophilic silica nanoparticles in 35-55 parts of toluene and stirring, then adding 9.115-31.9025 parts of a silane coupling agent, heating and stirring the suspension, washing after centrifugation, and drying in an oven;
[0019] Step 2: Preparation of modified silicone resin:
[0020] A vinyl silane coupling agent and a phenyl-containing silane coupling agent in a molar ratio of 2.5:1 to 4.5:1 are mixed with a deionized KOH solution, fully hydrolyzed, the reaction system is gradually heated, and phenyl vinyl silicone resin PASR is obtained by distillation. After adding toluene for dilution, a cation exchange resin is used to remove the strong alkaline substances in PASR, and the liquid is vacuum distilled to remove the toluene after filtering;
[0021] PASR phenylene silicone resin, acrylic acid, acrylamide, vinyl epoxy compound, and vinyl-terminated polydimethylsiloxane in a mass ratio of 1.15-2:0.05-0.16:0.12-0.28:0.9-2.3:2.34-4 are mixed, a catalyst is added dropwise after stirring evenly, and the mixture is fully stirred at room temperature and heated to obtain a modified silicone resin;
[0022] Step 3, preparation of super hydrophobic coating:
[0023] The modified PASR is diluted with 99.5wt% ester solvent and 99.0wt% aromatic hydrocarbon solvent in a mass ratio of 1:1, and stirred thoroughly; according to the mass ratio of modified PASR, modified silica, and micron-sized zirconia particles: 20-30: 8-15: 0.56-1.05, the modified silica and micron-sized zirconia particles are added, mixed thoroughly, and then additives are added and stirred thoroughly to obtain a fluorine-free wear-resistant super hydrophobic coating.
[0024] The aforementioned method for preparing a fluorine-free wear-resistant super-hydrophobic coating that can be applied to a heat exchanger, wherein the thickness of the fluorine-free wear-resistant super-hydrophobic coating is 46-65 μm.
[0025] The aforementioned method for preparing a fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger comprises the following preparation process:
[0026] Step 1, preparation of modified silica:
[0027] 8 g of hydrophilic silica nanoparticles were dispersed in 52 g of toluene and stirred, then 25 ml of 3-aminopropylmethyldiethoxysilane was added, and the suspension was heated to 90°C and stirred for 14 h; the suspension was centrifuged at 8500 rpm for 20 min, washed with ethanol, and finally dried in an oven at 85°C for 10 h;
[0028] Step 4: Preparation of modified silicone resin:
[0029] Under nitrogen atmosphere, 3-(methacryloyl chloride)propyltrimethoxysilane and methylphenyldimethoxysilane in a molar ratio of 3.5:1 and a deionized water solution of KOH were placed in a three-necked flask, fully stirred, and the silane coupling agent was hydrolyzed at 25°C for 45 minutes, and then the temperature was raised to 75°C to continue the reaction for 7 hours; then, the reaction system was gradually heated to 125°C, and low molecular weight fusel alcohols and generated water were distilled out to obtain phenylene silicone resin PASR; after PASR was cooled to room temperature, toluene was added to dilute it, and the strong alkaline substances in PASR were removed by cation exchange resin, and the obtained liquid was vacuum distilled to 130°C after filtration to remove toluene;
[0030] A mixture of PASR, acrylic acid, acrylamide, 4-vinylcyclohexene-1,2-epoxy, and vinyl-terminated polydimethylsiloxane in a mass ratio of 1.35:0.16:0.16:1.5:3.71 was slowly dripped into a three-necked flask, and after being stirred evenly, 0.13wt% azobisisobutylcyanide was added dropwise, and stirred vigorously at room temperature; the solution was then heated to 60°C, reacted for 1 hour, and the modified PASR was synthesized under a N2 atmosphere;
[0031] Step 3, preparation of super hydrophobic coating:
[0032] The modified PASR was diluted with a mixed solvent of butyl acetate and a commercial high-boiling point solvent in a mass ratio of 1:1, and stirred at room temperature for 0.5 h; according to the modified PASR, the modified silica and the micron-sized zirconia particles having a mass ratio of 20-30:8-15:0.56-1.05, the modified silica was added in small amounts gradually, stirred for 1.5 h, and then the micron-sized zirconia particles were added and fully mixed in an oscillator at 40°C water bath for 1 h; finally, 0.04 wt% of an organosilicon lubricant was added and fully stirred for 1 h to obtain a fluorine-free, wear-resistant and super-hydrophobic coating.
[0033] The present invention is beneficial in that:
[0034] The raw materials of the invention are environmentally friendly raw materials, and no fluorine reagent is modified or added, so the environmental protection cost is low.
[0035] The present invention uses modified silicone resin as a film-forming matrix, and the polydimethylsiloxane segment and the phenyl-containing silane segment in the polymer chain provide strong hydrophobicity. The trimethoxy / triethoxysilane silicone monomer can improve the crosslinking degree of the silicone resin and enhance the compactness of the coating; the dimethoxy / diethoxysilane silicone monomer can enhance the flexibility of the coating formed by the fluorine-free wear-resistant super-hydrophobic coating;
[0036] The carboxyl group and epoxy group introduced in the present invention can generate chemical bonds or hydrogen bonds and other weak interactions with metal ions, oxygen atoms or hydroxyl groups on the metal substrate, which can provide the required adhesion and can be compatible with a variety of metal substrates, thus solving the problem of low adhesion of silicone resin. At the same time, the epoxy group in the modified silicone resin provides abundant attack sites for SiO2 modified with the "N element" silane coupling agent, and the "amine-epoxy" click reaction is used to greatly improve the interaction between the coatings.
[0037] The coating obtained by the present invention has high hardness but toughness after curing, good corrosion resistance and good weather resistance; the components in the present invention work synergistically, while ensuring super hydrophobic performance, effectively solving the defects of poor adhesion and poor wear resistance of the organic silicon super hydrophobic coating, and significantly improving the application value;
[0038] The present invention achieves synergistic effect by modifying the modified silicon dioxide using a silane coupling agent containing "N element" and adding a phenyl-containing silane coupling agent in the synthesis of the silicone resin, so that the water contact angle of the super-hydrophobic coating prepared by the present invention can reach 162.12°, which can be used for frost suppression in heat exchangers. The super-hydrophobic surface can promote the jumping of condensed droplets, thereby delaying the growth of the frost layer; the super-hydrophobic surface can not only improve the condensation heat transfer efficiency, but also delay the heterogeneous nucleation of ice, reduce the density of the frost layer and significantly reduce the frost accumulation rate; the super-hydrophobic surface can also improve the defrosting efficiency by reducing the adhesion between the frost layer and the substrate surface, thereby more effectively removing condensed water and defrosting residual water. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The static contact angle diagram of the coating surface was analyzed by using ImageJ-Drop analysis on the sprayed samples of each embodiment;
[0040] Figure 2 The friction resistance test (2a) and the result diagram (2b) of the coatings of each embodiment after spraying, drying and standing for seven days on an aluminum plate;
[0041] Figure 3 Based on the optimal coating sprayed in Example 4, the effect of the number of frosting and defrosting cycles on the static contact angle is explored;
[0042] Figure 4 This is a schematic diagram of spraying the optimal coating on the heat exchanger and exploring the effect of the number of frosting and defrosting cycles on the frost suppression time. DETAILED DESCRIPTION
[0043] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0044] The preparation mechanism of modified silicone resin is as follows:
[0045]
[0046] The preparation mechanism of hydrophilic SiO2 modified and fluorine-free wear-resistant super hydrophobic coating is as follows;
[0047]
[0048] Example 1
[0049] (1) Preparation of modified silica:
[0050] 9 g of hydrophilic silica nanoparticles were dispersed in 52 g of toluene and stirred, and then 20 ml of 3-aminopropyltrimethoxysilane was added. The suspension was heated to 90°C and stirred for 14 h. The suspension was centrifuged (8500 rpm, 20 min), washed with ethanol, and finally dried in an oven at 85°C for 10 h.
[0051] (2) Preparation of modified silicone resin:
[0052] Under nitrogen atmosphere, 3-(methacryloyl chloride)propyltrimethoxysilane and methylphenyldimethoxysilane in a molar ratio of 3.5:1 and a deionized aqueous solution of KOH were placed in a three-necked flask, stirred thoroughly, and the silane coupling agent was hydrolyzed at 25°C for 45 minutes, and then the temperature was raised to 75°C for further reaction for 7 hours. Then, the reaction system was gradually heated to 125°C, and low molecular weight fusel alcohols and the generated water were distilled to obtain phenylene silicone resin (PASR). After the PASR was cooled to room temperature and diluted with toluene, the strong alkaline substances in the PASR were removed with a cation exchange resin, and the resulting liquid was vacuum distilled to 130°C after filtration to remove toluene.
[0053] A mixture of PASR, acrylic acid, acrylamide, 4-vinylcyclohexene-1,2-epoxy, and vinyl-terminated polydimethylsiloxane in a mass ratio of (1.35:0.16:0.16:1.5:3.71) was slowly dripped into a three-necked flask, and after being stirred evenly, 0.13wt% azobisisobutyl cyanide was added dropwise, and vigorously stirred at room temperature. The solution was then heated to 60°C, reacted for 1 hour, and the modified PASR was synthesized under a N2 atmosphere.
[0054] (3) Preparation of super hydrophobic coating:
[0055] The modified PASR was diluted with a mixed solvent of butyl acetate and a commercial high boiling point solvent in a mass ratio of 1:1 and stirred at room temperature for 0.5 h. According to the mass ratio of modified PASR, modified silica, and micron-sized zirconium oxide particles of 25:8:0.56, the modified silica was added in small amounts in succession, stirred for 1.5 h, and then the micron-sized zirconium oxide particles were added and fully mixed in an oscillator at 40°C water bath for 1 h. Finally, 0.04 wt% of an organosilicon lubricant was added and fully stirred for 1 h to obtain a fluorine-free wear-resistant super hydrophobic coating.
[0056] The coating prepared in Example 1 was sprayed onto a metal substrate to form a 55 μm thick fluorine-free wear-resistant super hydrophobic coating. The coating hardness was 2H, the coating adhesion was level 3, and the 3M tape could be peeled off 12 times.
[0057] Comparative Example 1
[0058] (1) Preparation of modified silica:
[0059] 8 g of hydrophilic silica nanoparticles were dispersed in 52 g of toluene and stirred, and then 25 ml of isopropyltriethoxysilane was added. The suspension was heated to 90°C and stirred for 14 h. The suspension was centrifuged (8500 rpm, 20 min), washed with ethanol, and finally dried in an oven at 85°C for 10 h.
[0060] (2) Preparation of modified silicone resin:
[0061] Under nitrogen atmosphere, a certain amount of 3-(methacryloyl chloride)propylmethyldimethoxysilane and a deionized water solution of KOH were placed in a three-necked flask, stirred thoroughly, and the silane coupling agent was hydrolyzed at 25°C for 45 minutes, and then the temperature was raised to 75°C to continue the reaction for 7 hours. Then, the reaction system was gradually heated to 125°C, and low molecular weight fusel alcohols and the generated water were distilled to obtain phenyl vinyl silicone resin (PASR). After the PASR was cooled to room temperature, toluene was added to dilute it, and the strong alkaline substances in the PASR were removed by cation exchange resin. After filtering, the obtained liquid was vacuum distilled to 130°C to remove toluene.
[0062] A mixture of silicone resin, acrylic acid, acrylamide, 4-vinylcyclohexene-1,2-epoxy, and vinyl-terminated polydimethylsiloxane in a mass ratio of (3.075:0.16:0.2:0.9:2.34) was slowly dripped into a three-necked flask, and after being stirred evenly, 0.13wt% azobisisobutyl cyanide was added dropwise, and vigorously stirred at room temperature. The solution was then heated to 60°C, reacted for 1 hour, and the modified PASR was synthesized under a N2 atmosphere.
[0063] (3) Preparation of super hydrophobic coating:
[0064] The modified PASR was diluted with a mixture of an ester solvent and an aromatic hydrocarbon solvent in a mass ratio of 1:1 and stirred at room temperature for 1.5 hours. According to the mass ratio of modified PASR, modified silica, and micron-sized zirconium oxide particles of 25:9:0.63, the modified silica was added in small amounts in succession, stirred for 1.5 hours, and then the micron-sized zirconium oxide particles were added and fully mixed in an oscillator at 40°C water bath for 1 hour. Finally, 0.04wt% of an organosilicon lubricant was added and fully stirred for 1 hour to obtain a fluorine-free wear-resistant super hydrophobic coating.
[0065] The difference between this comparative example 1 and the following examples is that: first, the modified silica is modified using a silane coupling agent that does not contain "N element" and second, no phenyl-containing silane coupling agent is added during the synthesis of the organic silicone resin.
[0066] The coating prepared in Comparative Example 1 was sprayed onto a metal substrate to form a 55 μm thick fluorine-free wear-resistant super hydrophobic coating. The coating hardness was H, the coating adhesion was level 4, and the 3M tape could be peeled off 7 times.
[0067] Comparative Example 2
[0068] (1) Preparation of modified silica:
[0069] 8 g of hydrophilic silica nanoparticles were dispersed in 51.96 g of toluene and stirred, and then 25 ml of 3-aminopropylmethyldiethoxysilane was added. The suspension was heated to 90°C and stirred for 14 h. The suspension was centrifuged (8500 rpm, 20 min), filtered, washed with ethanol, and finally dried in an oven at 85°C for 10 h.
[0070] (2) Preparation of modified silicone resin:
[0071] Under nitrogen atmosphere, 70g of 3-(methacryloyl chloride)propyltrimethoxysilane and a deionized water solution of KOH were placed in a three-necked flask, stirred thoroughly, and the silane coupling agent was hydrolyzed at 25°C for 45 minutes, and then the temperature was raised to 75°C and the reaction was continued for 7 hours. Then, the reaction system was gradually heated to 125°C, and low molecular weight fusel alcohols and the generated water were distilled to obtain alkenyl siloxane polymers. After cooling to room temperature, toluene was added for dilution, and the alkaline substances in the reaction were removed with a cation exchange resin. After filtering, the obtained liquid was vacuum distilled to 130°C to remove toluene.
[0072] A mixture of silicone resin, acrylic acid, acrylamide, and vinyl-terminated polydimethylsiloxane in a mass ratio of (1.5:0.12:0.24:3.71) was slowly dripped into a three-necked flask, and after being stirred evenly, 0.04wt% azobisisobutyl cyanide was added dropwise, and stirred vigorously at room temperature. The solution was then heated to 60°C, reacted for 1 hour, and the modified silicone resin was synthesized under a N2 atmosphere.
[0073] (3) Preparation of super hydrophobic coating:
[0074] The modified silicone resin was diluted with a mixed solvent of butyl acetate and a commercial high boiling point solvent in a mass ratio of 1:1 and stirred at room temperature for 0.5 h. According to the mass ratio of modified PASR, modified silica, and micron-sized zirconium oxide particles of 25:8:0.56, the modified silica was added in small amounts in succession, stirred for 1.5 h, and then the micron-sized zirconium oxide particles were added and fully mixed in an oscillator at 40°C water bath for 1 h. Finally, 0.04 wt% of silicone lubricant was added and fully stirred for 1 h to obtain a fluorine-free wear-resistant super hydrophobic coating.
[0075] The coating prepared in Example 2 was sprayed onto a metal substrate to form a 55 μm thick fluorine-free wear-resistant super hydrophobic coating. The coating hardness was 1H, the coating adhesion was level 3, and the 3M tape could be peeled off 15 times.
[0076] The difference between this comparative example 2 and the following examples is that no phenyl-containing silane coupling agent is added in the synthesis of the silicone resin.
[0077] Example 3
[0078] (1) Preparation of modified silica:
[0079] 8 g of hydrophilic silica nanoparticles were dispersed in 35 g of toluene and stirred, and then 35 ml of 3-aminopropyltrimethoxysilane was added. The suspension was heated to 90°C and stirred for 14 h. The suspension was centrifuged (8500 rpm, 20 min), washed with ethanol, and finally dried in an oven at 85°C for 10 h.
[0080] (2) Preparation of modified silicone resin:
[0081] Under nitrogen atmosphere, 3-(methacryloyl chloride)propyltrimethoxysilane and methylphenyldimethoxysilane in a molar ratio of 3.5:1 and a deionized aqueous solution of KOH were placed in a three-necked flask, stirred thoroughly, and the silane coupling agent was hydrolyzed at 25°C for 45 minutes, and then the temperature was raised to 75°C for further reaction for 7 hours. Then, the reaction system was gradually heated to 125°C, and low molecular weight fusel alcohols and the generated water were distilled to obtain phenylvinyl silicone resin (PASR). After the PASR was cooled to room temperature and diluted with toluene, the strong alkaline substances in the PASR were removed with a cation exchange resin, and the resulting liquid was vacuum distilled to 130°C after filtration to remove toluene.
[0082] A mixture of PASR, acrylic acid, acrylamide, and vinyl-terminated polydimethylsiloxane in a mass ratio of (1.8:0.08:0.24:3.5) was slowly dripped into a three-necked flask, and after being stirred evenly, 0.2wt% azobisisobutyl cyanide was added dropwise, and vigorously stirred at room temperature. The solution was then heated to 60°C, reacted for 1 hour, and the modified PASR was synthesized under a N2 atmosphere.
[0083] (3) Preparation of super hydrophobic coating:
[0084] The modified PASR was diluted with a mixture of an ester solvent and an aromatic hydrocarbon solvent in a mass ratio of 1:1 and stirred at room temperature for 1.5 hours. According to the mass ratio of modified PASR, modified silica, and micron-sized zirconium oxide particles of 25:8:0.56, the modified silica was added in small amounts in succession, stirred for 1.5 hours, and then the micron-sized zirconium oxide particles were added and fully mixed in an oscillator at 40°C water bath for 1 hour. Finally, 0.04wt% of an organosilicon slip agent was added and fully stirred for 1 hour to obtain a fluorine-free wear-resistant super hydrophobic coating.
[0085] The coating prepared in Example 3 was sprayed onto a metal substrate to form a 55 μm thick fluorine-free wear-resistant super hydrophobic coating. The coating hardness was 2H, the coating adhesion was level 2, and the 3M tape could be peeled off 14 times.
[0086] Example 4
[0087] (1) Preparation of modified silica:
[0088] 8 g of hydrophilic silica nanoparticles were dispersed in 52 g of toluene and stirred, and then 25 ml of 3-aminopropylmethyldiethoxysilane was added. The suspension was heated to 90°C and stirred for 14 h. The suspension was centrifuged (8500 rpm, 20 min), washed with ethanol, and finally dried in an oven at 85°C for 10 h.
[0089] (2) Preparation of modified silicone resin:
[0090] Under nitrogen atmosphere, 3-(methacryloyl chloride)propyltrimethoxysilane and methylphenyldimethoxysilane in a molar ratio of 3.5:1 and a deionized aqueous solution of KOH were placed in a three-necked flask, stirred thoroughly, and the silane coupling agent was hydrolyzed at 25°C for 45 minutes, and then the temperature was raised to 75°C for further reaction for 7 hours. Then, the reaction system was gradually heated to 125°C, and low molecular weight fusel alcohols and the generated water were distilled to obtain phenylvinyl silicone resin (PASR). After the PASR was cooled to room temperature and diluted with toluene, the strong alkaline substances in the PASR were removed with a cation exchange resin, and the resulting liquid was vacuum distilled to 130°C after filtration to remove toluene.
[0091] A mixture of PASR, acrylic acid, acrylamide, 4-vinylcyclohexene-1,2-epoxy, and vinyl-terminated polydimethylsiloxane in a mass ratio of (1.35:0.16:0.16:1.5:3.71) was slowly dripped into a three-necked flask, and after being stirred evenly, 0.13wt% azobisisobutyl cyanide was added dropwise, and vigorously stirred at room temperature. The solution was then heated to 60°C, reacted for 1 hour, and the modified PASR was synthesized under a N2 atmosphere.
[0092] (3) Preparation of super hydrophobic coating:
[0093] The modified PASR was diluted with a mixed solvent of butyl acetate and a commercial high boiling point solvent in a mass ratio of 1:1 and stirred at room temperature for 0.5 h. According to the mass ratio of modified PASR, modified silica, and micron-sized zirconia particles of 25:8:0.56, the modified silica was added in small amounts in succession and stirred for 1.5 h. The micron-sized zirconia particles were added and fully mixed in an oscillator at 40°C water bath for 1 h. Finally, 0.04 wt% of an organosilicon lubricant was added and fully stirred for 1 h to obtain a fluorine-free wear-resistant super hydrophobic coating.
[0094] The coating prepared in Example 4 was sprayed onto a metal substrate to form a 55 μm thick fluorine-free wear-resistant super hydrophobic coating. The coating hardness was 4H, the coating adhesion was level 0, and the 3M tape could be peeled off 29 times.
[0095] Example 5
[0096] (1) Preparation of modified silica:
[0097] 15 g of hydrophilic silica nanoparticles were dispersed in 55 g of toluene and stirred, and then 22 ml of 3-aminopropylmethyldiethoxysilane was added. The suspension was heated to 90°C and stirred for 14 h. The suspension was centrifuged (8500 rpm, 20 min), washed with ethanol, and finally dried in an oven at 85°C for 10 h.
[0098] (2) Preparation of modified silicone resin:
[0099] Under nitrogen atmosphere, 3-(methacryloyl chloride)propyltrimethoxysilane and methylphenyldimethoxysilane in a molar ratio of 4.5:1 and a deionized water solution of KOH were placed in a three-necked flask, stirred thoroughly, and the silane coupling agent was hydrolyzed at 25°C for 45 minutes, and then the temperature was raised to 75°C for further reaction for 7 hours. Then, the reaction system was gradually heated to 125°C, and low molecular weight fusel alcohols and the generated water were distilled to obtain phenylvinyl silicone resin (PASR). After the PASR was cooled to room temperature and diluted with toluene, the strong alkaline substances in the PASR were removed with a cation exchange resin, and the resulting liquid was vacuum distilled to 130°C after filtration to remove toluene.
[0100] A mixture of PASR, acrylic acid, acrylamide, 4-vinylcyclohexene-1,2-epoxy, and vinyl-terminated polydimethylsiloxane in a mass ratio of (1.5:0.05:0.28:0.9:4) was slowly dripped into a three-necked flask, and after being stirred evenly, 0.15wt% azobisisobutyl cyanide was added dropwise, and stirred vigorously at room temperature. The solution was then heated to 60°C, reacted for 1 hour, and the modified PASR was synthesized under a N2 atmosphere.
[0101] (3) Preparation of super hydrophobic coating:
[0102] The modified PASR was diluted with a mixed solvent of butyl acetate and a commercial high-boiling point solvent in a mass ratio of 1:1 and stirred at room temperature for 0.5 h. According to the mass ratio of modified PASR, modified silica, and micron-sized zirconia particles of 30:15:1.5, the modified silica was added in small amounts in succession, stirred for 1.5 h, and then the micron-sized zirconia particles were added and fully mixed in an oscillator at 40°C water bath for 1 h. Finally, 0.06 wt% of an organosilicon slip agent was added and fully stirred for 1 h to obtain a fluorine-free wear-resistant super hydrophobic coating.
[0103] The coating prepared in Example 5 was sprayed onto a metal substrate to form a 55 μm thick fluorine-free wear-resistant super hydrophobic coating. The coating hardness was 1H, the coating adhesion was level 3, and the 3M tape could be peeled off 11 times.
[0104] Example 6
[0105] (1) Preparation of modified silica:
[0106] 12 g of hydrophilic silica nanoparticles were dispersed in 35 g of toluene and stirred, and then 28 ml of 3-aminopropylmethyldiethoxysilane was added. The suspension was heated to 90°C and stirred for 14 h. The suspension was centrifuged (8500 rpm, 20 min), washed with ethanol, and finally dried in an oven at 85°C for 10 h.
[0107] (2) Preparation of modified silicone resin:
[0108] Under nitrogen atmosphere, 3-(methacryloyl chloride)propyltrimethoxysilane and methylphenyldimethoxysilane in a molar ratio of 3:1 and a deionized water solution of KOH were placed in a three-necked flask, stirred thoroughly, and the silane coupling agent was hydrolyzed at 25°C for 45 minutes, and then the temperature was raised to 75°C for further reaction for 7 hours. Then, the reaction system was gradually heated to 125°C, and low molecular weight fusel alcohols and the generated water were distilled to obtain phenylvinyl silicone resin (PASR). After the PASR was cooled to room temperature and diluted with toluene, the strong alkaline substances in the PASR were removed with a cation exchange resin, and the resulting liquid was vacuum distilled to 130°C after filtration to remove toluene.
[0109] A mixture of PASR, acrylic acid, acrylamide, 4-vinylcyclohexene-1,2-epoxy, and vinyl-terminated polydimethylsiloxane in a mass ratio of (1.85:0.16:0.12:2.3:4) was slowly dripped into a three-necked flask, and after being stirred evenly, 0.04wt% azobisisobutyl cyanide was added dropwise, and stirred vigorously at room temperature. The solution was then heated to 60°C, reacted for 1 hour, and the modified PASR was synthesized under a N2 atmosphere.
[0110] (3) Preparation of super hydrophobic coating:
[0111] The modified PASR was diluted with a mixed solvent of butyl acetate and a commercial high boiling point solvent in a mass ratio of 1:1 and stirred at room temperature for 0.5 h. According to the mass ratio of modified PASR, modified silica, and micron-sized zirconia particles of 29:14:0.28, the modified silica was added in small amounts in succession and stirred for 1.5 h. The micron-sized zirconia particles were added and fully mixed in an oscillator at 40°C water bath for 1 h. Finally, 0.02 wt% of an organosilicon lubricant was added and fully stirred for 1 h to obtain a fluorine-free wear-resistant super hydrophobic coating.
[0112] The coating prepared in Example 6 was sprayed onto a metal substrate to form a 55 μm thick fluorine-free wear-resistant super hydrophobic coating. The coating hardness was 2H, the coating adhesion was level 3, and the 3M tape could be peeled off 13 times.
[0113] Example 7
[0114] (1) Preparation of modified silica:
[0115] 7 g of hydrophilic silica nanoparticles were dispersed in 45 g of toluene and stirred, and then 30 ml of N-(2-aminoethyl-3-aminopropyl)trimethoxysilane was added. The suspension was heated to 90°C and stirred for 14 h. The suspension was centrifuged (8500 rpm, 20 min), washed with ethanol, and finally dried in an oven at 85°C for 10 h.
[0116] (2) Preparation of modified silicone resin:
[0117] Under nitrogen atmosphere, 3-(methacryloyl chloride)propyltrimethoxysilane and methylphenyldimethoxysilane in a molar ratio of 2.5:1 and a deionized aqueous solution of KOH were placed in a three-necked flask, stirred thoroughly, and the silane coupling agent was hydrolyzed at 25°C for 45 minutes, and then the temperature was raised to 75°C for further reaction for 7 hours. Then, the reaction system was gradually heated to 125°C, and low molecular weight fusel alcohols and the generated water were distilled to obtain phenylvinyl silicone resin (PASR). After the PASR was cooled to room temperature and diluted with toluene, the strong alkaline substances in the PASR were removed with a cation exchange resin, and the resulting liquid was vacuum distilled to 130°C after filtration to remove toluene.
[0118] A mixture of PASR, acrylic acid, acrylamide, 4-vinylcyclohexene-1,2-epoxy, and vinyl-terminated polydimethylsiloxane in a mass ratio of (2:0.16:0.25:2.1:3.67) was slowly dripped into a three-necked flask, and after being stirred evenly, 0.2wt% azobisisobutyl cyanide was added dropwise, and stirred vigorously at room temperature. The solution was then heated to 60°C, reacted for 1 hour, and the modified PASR was synthesized under a N2 atmosphere.
[0119] (3) Preparation of super hydrophobic coating:
[0120] The modified PASR was diluted with a mixed solvent of butyl acetate and a commercial high boiling point solvent in a mass ratio of 1:1 and stirred at room temperature for 0.5 h. According to the mass ratio of modified PASR, modified silica, and micron-sized zirconium oxide particles of 20:8:0.64, the modified silica was added in small amounts in succession, stirred for 1.5 h, and then the micron-sized zirconium oxide particles were added and fully mixed for 1 h in an oscillator at 40°C water bath. Finally, 0.06 wt% of an organosilicon slip agent was added and fully stirred for 1 h to obtain a fluorine-free wear-resistant super hydrophobic coating.
[0121] The coating prepared in Example 7 was sprayed onto a metal substrate to form a 55 μm thick fluorine-free wear-resistant super hydrophobic coating. The coating hardness was 2H, the coating adhesion was level 1, and the 3M tape could be peeled off 16 times.
[0122] Experimental verification:
[0123] The coatings prepared in Comparative Example 1, Comparative Example 2, Example 1, Example 3, and Example 4 were sprayed onto a metal substrate, and after drying, the droplet shapes were analyzed using ImageJ-Drop analysis ( Figure 1 ). Tests have shown that Example 1 ( Figure 1 a), Comparative Example 1 ( Figure 1 b), Comparative Example 2 ( Figure 1 c), Example 3 ( Figure 1 d) and Example 4 ( Figure 1 e) The static contact angles are 156.11°, 117.41°, 142.97°, 159.88° and 162.12° respectively.
[0124] In order to further examine the mechanical durability of the coating surface, the cyclic friction number-contact angle test was used to determine the durability, with the friction number and static contact angle as indicators. The friction test used 1000-grit sandpaper, with the test surface facing down and a 100g weight as the test load ( Figure 2 a), a horizontal uniform force of 28 cm is regarded as one friction cycle, and the contact angle change is measured every 10 cycles.
[0125] The modification of different silane coupling agents showed different wear resistance of the coating. When the surface of the coating of Example 1 was rubbed 70 times, the static contact angle remained above 150° ( Figure 2 b). When the coating surface of Example 3 was rubbed 50 times, the static contact angle was still above 150° ( Figure 2 b). After 60 times, the static contact angle of the coating surface of Example 3 is 146.65°. After 140 times of friction, the static contact angle of the coating surface of Example 4 is still above 150° ( Figure 2b). It can be seen that the coatings obtained by the formula of the present invention have good wear resistance. The micron-sized ZrO2 particles can be used as Lewis acid to effectively promote the ammonia-epoxy "click" reaction in the preparation of the coating, connect different components through chemical bonds, effectively enhance the interaction between the coatings, and thus enhance the wear resistance of the coating surface. Example 4 is the best example.
[0126] The test shows that the coating hardness of Example 4 is 4H, the coating adhesion is level 0, and the 3M tape is peeled off 29 times. Using 1000-mesh sandpaper and a 100g weight as a load, the coating can be rubbed for 39m cycles, and the static contact angle is still maintained above 150°. In the subsequent performance test, the frosting and defrosting cycle test under this ratio state is studied.
[0127] The test conditions are an ambient temperature of 20°C, a refrigeration table temperature of -8°C, and an indoor relative humidity of 60%. Complete frosting and defrosting and drying is considered a cycle, and data is recorded every five cycles. The effect of the number of frosting and defrosting cycles on the static contact angle of the coating surface is explored. When the uncoated aluminum plate is subjected to frosting and defrosting tests, the surface of the aluminum plate is observed through an industrial microscope. As the temperature of the aluminum plate decreases, the droplets gradually condense and gradually form ice crystals. At 8 minutes, all the water droplets are frozen and form a frost layer.
[0128] Within 60 cycles of frosting and defrosting, the static contact angle of the coating surface can still be maintained above 160° ( Figure 3 ). With the increase of the number of frosting and defrosting cycles, the static contact angle can remain stable over a longer range. This is because the coating surface provides limited nucleation sites for the formation of uneven ice crystals, and the "air cavity" formed by the micro-nano structure effectively delays the appearance of ice crystals, thereby reducing frosting or hindering the adhesion of the frost layer, greatly reducing the damage to the coating surface.
[0129] The coating of Example 4 was sprayed on the heat exchanger to explore the effect of fluorine-free wear-resistant super hydrophobicity on the frost inhibition time. Figure 4 As shown. The ambient temperature is 20℃, the indoor relative humidity is 60%, the outlet temperature of the high and low temperature all-in-one machine is -15℃, and the flow rate is 8L / min. The fan model is TX17250H24B, and the air volume is 368.0CFM. The wind speed is tested at 5 random points on the heat exchanger. When the wind speed at all 5 points is 0, the heat exchanger is considered to be completely frosted. After complete frosting and defrosting and drying, it is considered a cycle, and data is recorded every five cycles. The specific parameters of the heat exchanger are shown in Table 1.
[0130] Heat exchanger type Fin Type Pitch Hole spacing Number of rows Number of holes Fin length Pipe diameter Core length Tube-fin Flat sheet 1.5mm 20mm 2 rows 16 168mm 7mm 180mm
[0131] Table 1. Specific parameters of heat exchanger
[0132] When the uncoated heat exchanger was tested for frost inhibition, the wind speed at the five positions was all 0 after 8.5 minutes. After spraying the fluorine-free wear-resistant super-hydrophobic coating, the longest frost inhibition time was 26.7 minutes. During the first 75 frosting and defrosting cycles, the frost inhibition time could be maintained at more than 25 minutes. After the number of frosting and defrosting cycles reached 80 times, the frost inhibition time of the heat exchanger dropped sharply. When the number of frosting and defrosting cycles reached 105 times, the volume expansion of the ice crystals may cause mechanical damage to the micro-nano structure of the coating surface, and the coating surface loses its super-hydrophobic properties. The water droplets on the coating surface undergo a transition from the Cassie state to the Wenzel state, which increases the adhesion of the water droplets on the surface, making it difficult for the droplets to detach from the surface before ice crystals are formed, and lose their frost inhibition properties.
[0133] In summary, the present invention uses modified silicone resin as a film-forming matrix, and the polydimethylsiloxane segment and the phenyl silane segment in the polymer chain synergistically provide a strong hydrophobic ability to enhance the density and flexibility of the coating; the carboxyl group and epoxy group introduced in the present invention can react with the metal ions on the metal substrate to solve the problem of low adhesion of silicone resin; the coating obtained by the present invention has high hardness but toughness after curing, good corrosion resistance and good weather resistance; the modified silicon dioxide in the present invention is modified by a silane coupling agent containing "N element", and the silicone A phenyl-containing silane coupling agent is added during the synthesis of the resin to achieve a synergistic effect, so that the water contact angle of the super-hydrophobic coating prepared by the present invention can reach 162.12°, and can be used for frost suppression of heat exchangers to promote the jumping of condensed droplets, thereby delaying the growth of the frost layer; the super-hydrophobic surface can not only improve the condensation heat transfer efficiency, but also delay the heterogeneous nucleation of ice, reduce the density of the frost layer and significantly reduce the frost accumulation rate; the super-hydrophobic surface can also improve the defrosting efficiency by reducing the adhesion between the frost layer and the substrate surface, thereby more effectively removing condensed water and defrosting residual water.
[0134] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger, characterized in that: The formula includes by mass ratio: 20- 30:8-15:0.56-1.05 modified PASR, modified silicon dioxide, micron-sized zirconium oxide particles; the modified PASR formula includes: phenyl vinyl silicone resin PASR, acrylic acid, acrylamide, vinyl epoxy compound, vinyl-terminated polydimethylsiloxane in a mass ratio range of 1.15-2:0.05-0.16:0.12-0.28:0.9-2.3:2.34-4.
2. The fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger according to claim 1, characterized in that: The modified PASR formula further comprises: a catalyst; the catalyst is azobisisobutyl cyanide with a mass fraction of 0.04-0.2wt%.
3. The fluorine-free wear-resistant super hydrophobic coating applicable to a heat exchanger according to claim 1, characterized in that: The phenyl alkenyl silicone resin PASR is prepared from a vinyl silane coupling agent and a phenyl-containing silane coupling agent in a molar ratio of 2.5:1-4.5:
1.
4. The fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger according to claim 1, characterized in that: The modified silica is prepared by dispersing 7-15 parts of hydrophilic silica nanoparticles in 35-55 parts of toluene and stirring, then adding 9.115-31.9025 parts of a silane coupling agent containing "N element", and then heating, stirring, centrifuging, washing, and drying.
5. The fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger according to claim 4, characterized in that: The silane coupling agent containing "N element" is 3-aminopropyltriethoxysilane, diethylenetriaminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl-3-aminopropyl)methyldimethoxysilane, N-(2-aminoethyl-3-aminopropyl)trimethoxysilane, amino-terminated polydimethylsiloxane, 3-(methacryloyl chloride)propyltrimethoxysilane, or 3-(methacryloyl chloride)propylmethyldimethoxysilane, or a combination of several thereof.
6. The fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger according to claim 1, characterized in that: Also includes: 0.02-0.07wt% of auxiliary agents, the auxiliary agents include: dispersant, defoamer, and silicone lubricant.
7. The fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger according to claim 1, characterized in that: Also includes: A solvent mixture for diluting the modified PASR, wherein the solvent mixture is 99.5wt% of an ester solvent and 99.0wt% of an aromatic hydrocarbon solvent in a mass ratio of 1:1; the ester solvent comprises one or a combination of ethyl acetate, n-propyl acetate, butyl acetate or isobutyl acetate; and the aromatic hydrocarbon solvent is one or a combination of toluene or xylene.
8. A method for preparing a fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger, characterized in that: The preparation process includes the following steps: Step 1, preparation of modified silica: Dispersing 7-15 parts of hydrophilic silica nanoparticles in 35-55 parts of toluene and stirring, then adding 9.115-31.9025 parts of a silane coupling agent, heating and stirring the suspension, washing after centrifugation, and drying in an oven; Step 2, preparation of modified silicone resin: A vinyl silane coupling agent and a phenyl-containing silane coupling agent in a molar ratio of 2.5:1-4.5:1 are mixed with a deionized water solution of KOH, and fully hydrolyzed. The reaction system is gradually heated and distilled to obtain a phenyl vinyl silicone resin PASR. After diluting with toluene, a cation exchange resin is used to remove the strong alkaline substance in the PASR, and the liquid is vacuum distilled to remove the toluene after filtering; PASR phenylene silicone resin, acrylic acid, acrylamide, vinyl epoxy compound, and vinyl-terminated polydimethylsiloxane in a mass ratio of 1.15-2:0.05-0.16:0.12-0.28:0.9-2.3:2.34-4 are mixed, a catalyst is added dropwise after stirring evenly, and the mixture is fully stirred at room temperature and heated to obtain a modified silicone resin; Step 3: Preparation of super hydrophobic coating: The modified PASR is diluted by mixing 99.5wt% ester solvent and 99.0wt% aromatic hydrocarbon solvent in a mass ratio of 1:1, and stirred thoroughly; according to the mass ratio of modified PASR, modified silica, and micron-sized zirconia particles being 20-30:8-15:0.56-1.05, the modified silica and micron-sized zirconia particles are added, mixed thoroughly, and then additives are added and stirred thoroughly to obtain a fluorine-free wear-resistant super hydrophobic coating.
9. The method for preparing a fluorine-free wear-resistant super-hydrophobic coating applicable to a heat exchanger according to claim 8, characterized in that: The preparation process includes the following: Step 1, preparation of modified silica: 8 g of hydrophilic silica nanoparticles were dispersed in 52 g of toluene and stirred, and then 22.7875 g of 3-aminopropylmethyldiethoxysilane was added, and the suspension was heated to 90° C. and stirred for 14 h; the suspension was centrifuged at 8500 rpm for 20 min, washed with ethanol, and finally dried in an oven at 85° C. for 10 h; Step 2: Preparation of modified silicone resin: Under nitrogen atmosphere, 3-(methacryloyl chloride)propyltrimethoxysilane and methylphenyldimethoxysilane in a molar ratio of 3.5:1 and a deionized water solution of KOH were placed in a three-necked flask, fully stirred, and the silane coupling agent was hydrolyzed at 25°C for 45 minutes, and then the temperature was raised to 75°C to continue the reaction for 7 hours; then, the reaction system was gradually heated to 125°C, and low molecular weight fusel alcohols and generated water were distilled off to obtain phenylene silicone resin PASR; after the PASR was cooled to room temperature, toluene was added to dilute it, and the strong alkaline substances in the PASR were removed by a cation exchange resin, and the obtained liquid was vacuum distilled to 130°C after filtration to remove toluene; A mixture of PASR, acrylic acid, acrylamide, 4-vinylcyclohexene-1,2-epoxy, and vinyl-terminated polydimethylsiloxane in a mass ratio of 1.35:0.16:0.16:1.5:3.71 was slowly dripped into a three-necked flask, and after being stirred evenly, 0.13wt% of azobisisobutylcyanide was added dropwise, and stirred vigorously at room temperature; the solution was then heated to 60°C, reacted for 1 hour, and the modified PASR was synthesized under a N2 atmosphere; Step 3, preparation of super hydrophobic coating: The modified PASR was diluted with a mixed solvent of butyl acetate and a commercial high-boiling point solvent in a mass ratio of 1:1, and stirred at room temperature for 0.5 h; according to the mass ratio of modified PASR, modified silica, and micron-sized zirconia particles of 25:8:0.56, the modified silica was added in small amounts gradually, and after stirring for 1.5 h, the micron-sized zirconia particles were added, and the mixture was fully mixed in an oscillator at 40°C water bath for 1 h; finally, 0.04 wt% of an organosilicon lubricant was added, and the mixture was fully stirred for 1 h to obtain a fluorine-free, wear-resistant, super-hydrophobic coating.